Use of technical terms in German biology lessons and its effects on students' conceptual learning. Issue 2 (2nd April 2020) - Dorfner, Tobias; Förtsch, Christian; Neuhaus, Birgit J.
ABSTRACT: Educational standards and instructional frameworks aim to foster students' scientific literacy, especially their conceptual knowledge. Previous research has examined several instructional approaches to foster students' conceptual learning. Reliable and adequate use of technical terms in science instruction is also essential for fostering students' conceptual learning. However, current studies of the analyses of the use of technical terms and their effects on fostering students' conceptual understanding in biology lessons are lacking. In this study, we first conducted a descriptive analysis of the technical terms used in selected videotaped German 9 th -grade biology lessons ( N = 43) on neurobiology. Then, we conducted multilevel analyses of the effects of using different technical terms in a biology lesson on students' achievement and situational interest. Our descriptive results showed that on average teachers ( N = 43) talked more and used more technical terms compared to their students and that many different technical terms were used in our analysed lessons. Furthermore, our multilevel analyses showed negative effects of using a high number of different technical terms on both student outcome variables. We conclude that a well-considered, but simple, reduction of technical terms in biology lessons could positively affect students' learning of conceptual knowledge. Therefore, the findings in this study have implications that teachers should use minimally necessary topic-relevant technical terms in biology instruction with the additional use of biological core ideas. We suggest further research in pre-service and in-service teacher education programmes to evaluate teachers' effective use of technical terms in biology lessons essential for fostering conceptual learning.